Analisis Pemeriksaan IVA Test Pada Wanita Usia Subur Di Wilayah Kerja Puskesmas Muara - Novalia Eka Sari; Arie Wahyudi; Gema Asiani; Deby Utami Siska Ariani (Program Studi DIV Kebidanan Fakultas Ilmu Kesehatan Universitas Muhammadiyah Gorontalo, 2026)
Cervical cancer is one of the leading causes of female mortality that can be prevented through early detection using the Visual Inspection with Acetic Acid (VIA) method. This study aims to analyze the factors associated with VIA screening among women of reproductive age in the working area of the Muara Rupit Community Health Center in 2026. This study employed a cross-sectional design with a sample size of 371 women of reproductive age, aged between 30 and 50 years. Data were collected using questionnaires and analyzed univariately, bivariately using the Chi-Square test, and multivariately using multiple logistic regression. The bivariate analysis results indicated that knowledge (p-value = 0.033), attitude (p-value < 0.001), healthcare access (p-value < 0.001), husband's support (p-value < 0.001), and the role of healthcare workers (p-value < 0.001) were significantly associated with VIA screening among women of reproductive age. Healthcare access was the most dominant factor associated with VIA screening, with an Adjusted Odds Ratio (AOR) of 2.855 (95% CI: 1.683–4.844; p < 0.001). Knowledge, attitude, healthcare access, husband's support, and the role of healthcare workers were associated with VIA screening, with healthcare access being the most dominant factor. Therefore, efforts are required to improve healthcare access by ensuring ease of reach, facility availability, cost affordability, and transportation convenience to increase VIA screening coverage among women of reproductive age.